A high-resolution view of the filament of gas between Abell 399 and Abell 401 from the Atacama Cosmology Telescope and MUSTANG-2. Issue 3 (26th November 2021) - Hincks, Adam D; Radiconi, Federico; Romero, Charles; Madhavacheril, Mathew S; Mroczkowski, Tony; Austermann, Jason E; Barbavara, Eleonora; Battaglia, Nicholas; Battistelli, Elia; Bond, J Richard; Calabrese, Erminia; de Bernardis, Paolo; et al.
ABSTRACT: We report a significant detection of the hot intergalactic medium in the filamentary bridge connecting the galaxy clusters Abell 399 and Abell 401. This result is enabled by a low-noise, high-resolution map of the thermal Sunyaev–Zeldovich signal from the Atacama Cosmology Telescope (ACT) and Planck satellite. The ACT data provide the 1.65 arcmin resolution that allows us to clearly separate the profiles of the clusters, whose centres are separated by 37 arcmin, from the gas associated with the filament. A model that fits for only the two clusters is ruled out compared to one that includes a bridge component at >5σ. Using a gas temperature determined from Suzaku X-ray data, we infer a total mass of (3.3± 0.7)× 10^14 M_ associated with the filament, comprising about 8 per cent of the entire Abell 399–Abell 401 system. We fit two phenomenological models to the filamentary structure; the favoured model has a width transverse to the axis joining the clusters of 1.9 Mpc . When combined with the Suzaku data, we find a gas density of (0.88± 0.24)× 10^-4 cm^-3, considerably lower than previously reported. We show that this can be fully explained by a geometry in which the axis joining Abell 399 and Abell 401 has a large component along the line of sight, such that the distance between the clusters is significantly greater than the 3.2 Mpc projected separation on the plane of the sky. Finally, we present initial results from higher resolution (12.7 arcsec effective) imaging of the bridge with the MUSTANG-2 receiver on the Green Bank Telescope.